If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + x) = 5x + 54 (3 * 2 + x * 2) = 5x + 54 (6 + 2x) = 5x + 54 Reorder the terms: 6 + 2x = 54 + 5x Solving 6 + 2x = 54 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 2x + -5x = 54 + 5x + -5x Combine like terms: 2x + -5x = -3x 6 + -3x = 54 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + -3x = 54 + 0 6 + -3x = 54 Add '-6' to each side of the equation. 6 + -6 + -3x = 54 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = 54 + -6 -3x = 54 + -6 Combine like terms: 54 + -6 = 48 -3x = 48 Divide each side by '-3'. x = -16 Simplifying x = -16
| -6x-115=-14x+69 | | 18d+5d-20d=72 | | x-7=-5-22 | | x+80=2x+20 | | 29c+-10c+8=-11 | | bc-3g=2k | | log(x^2+4x+4)=2 | | -8p+5p=-78 | | 5+6z=17 | | 3+-4=44 | | -x+7x=171+x | | -1+((8-15)-(-15-4))= | | 3(4x+2)+1=28x+15 | | 6a+4a=8a-5 | | -6n=-60 | | -104+7x=17x+156 | | 5=-(z-10) | | (X-2+6x)+x=8x-2 | | 0+-2=x | | 0+y+12y=-26 | | 3a+3whena=9 | | 66s-59s-2s+11=96 | | 18y-6=66 | | -10x-21=-11x+14 | | 230h+x=1265 | | 2(xa+4)-5=2x+3 | | 5(2n-1)=-15 | | 0+y+12=-26 | | F+8=-8-f+10 | | 19a-10a-a-3a=10 | | (4x^2-3x-40)=0 | | x-2=7x-2 |